Virtual monochromatic image at lower energy level for assessing pancreatic ductal adenocarcinoma in fast kV-switching dual-energy CT. Issue 4 (April 2020) - Noda, Y.; Goshima, S.; Kaga, T.; Ando, T.; Miyoshi, T.; Kawai, N.; Kawada, H.; Tanahashi, Y.; Matsuo, M.
Abstract : AIM: To evaluate the value of virtual monochromatic images (VMIs) at lower energy levels in fast-voltage-switching dual-energy computed tomography (DECT) for assessing pancreatic ductal adenocarcinoma (PDAC). MATERIALS AND METHODS: The institutional review board approved this prospective study. Written informed consent was obtained from all patients. Seventy-four consecutive patients with PDAC underwent dynamic contrast-enhanced DECT. Two radiologists reviewed eight energy levels (40, 45, 50, 55, 60, 65, 70, and 75 keV) of the pancreatic parenchymal phase VMIs. CT attenuation of the PDAC and pancreatic parenchyma, background noise, signal-to-noise ratio (SNR) of the pancreas, tumour-to-pancreas contrast-to-noise ratio (CNR), major and minor axes of PDAC, and qualitative tumour conspicuity were compared among the VMIs at eight energy levels. RESULTS: CT attenuation of PDAC and pancreatic parenchyma, background noise, SNR, and CNR peaked on VMIs at 40 keV with statistically significant difference ( p< 0.0001) and gradually decreased with increasing energy levels. The reproducibility in measuring tumour size was better on VMIs at 40 keV (28.8 and 29.2 mm of major axis in readers 1 and 2, respectively) and tended to be overestimated at higher energy levels (29.8 and 30.9 mm of major axis at 75 keV in readers 1 and 2, respectively). Qualitative tumour conspicuity was also significantly superior on VMIs at 40 keV than at all other energy levels ( p< 0.0001). CONCLUSION: VMIs at 40 keV demonstrated significantly increased SNR of the pancreas, CNR, and tumour conspicuity and high reproducibility in measuring tumour size for assessing PDAC. Highlights: Dual-energy CT could be useful for assessing pancreatic ductal adenocarcinoma. The best SNR and CNR was obtained using 40 keV images. The reproducibility in measuring tumor size was better on 40 keV images.